Decentralized dynamic event‐triggered control for networked control systems under unreliable communication network and actuator saturation - Yang, Fan; Shen, Zhuan; Chen, Jing; Hu, Aihua; Zhang, Jingxiang; Hu, Manfeng (Asian journal of control, 2023)
In this paper, the stochastic stability of networked control systems (NCSs) with nonlinear perturbation and parameter uncertainties is studied. A decentralized dynamic event triggering scheme (DDETS) is introduced to reduce energy consumption and network transmission burden. Each channel can decide whether to transmit signals sampled by corresponding sensors through this mechanism. Due to the unreliability of communication network, a new mathematical model of NCSs based on multi‐channel fading and hybrid cyber attacks is established, and the actuator is constrained by saturation. A sufficient condition for stochastic stability based on static controller is derived through Lyapunov stability theory, and two numerical examples are given to demonstrate the effectiveness of the method.